Does Translanguaging Enhance Learning? Examining EFL Students’ Perceptions and Success in Bali - Ratminingsih, Ni Made; Padmadewi, Ni Nyoman; Nitiasih, Putu Kerti; Artini, Luh Putu; Ana, I Ketut Trika Adi (VELES Voices of English Language Education Society, 2024)
The integration of first and second languages in English as a Foreign Language (EFL) classrooms, termed translanguaging, is gaining recognition for its potential to improve comprehension and student engagement. This study investigates students’ perceptions of translanguaging in Bali, a unique multilingual setting, and examines its correlation with their English learning achievement. Bali’s sociolinguistic environment, where students frequently use Balinese, Indonesian, and English, offers an ideal context to explore this phenomenon. This study employed a correlational research design, involving 65 fourth-semester students aged 18 to 22, to assess perceptions of translanguaging through a structured questionnaire and their English achievement through standardized tests. Descriptive statistics showed that students held positive perceptions of translanguaging, finding it beneficial for understanding course content and encouraging participation. However, Pearson correlation analysis revealed a minimal, non-significant correlation between students’ positive perceptions and their English learning achievement (r = 0.039, sig. = 0.758). While translanguaging created a supportive and engaging learning environment, its direct influence on academic achievement was limited. These findings suggest that although translanguaging may foster an inclusive and interactive classroom setting, it does not significantly impact measurable language achievement. This study contributes valuable insights into the role of multilingual practices in EFL education and encourages further research on their complex effects on learning outcomes.